2019
DOI: 10.7600/jpfsm.8.73
|View full text |Cite
|
Sign up to set email alerts
|

Ice slurry ingestion as a cooling strategy in the heat

Abstract: It is well known that excessively elevated core body temperature owing to prolonged exercise in high temperatures causes heat-related illness and has a negative impact on exercise performance. Many articles have been published about effective cooling methods to avoid such impacts on physiological functions in the heat. Ice slurry ingestion has been used by many athletes as a practical and effective cooling strategy. Ice slurry can easily be used on sports fields. Moreover, ice slurry reduces core body temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The literature has shown the relevance of cooling strategies prior to exercise (pre-cooling) to limit the negative impact on aerobic performance [5][6][7][8]. Among these countermeasures, external (e.g., cooling vest, water immersion) and internal (e.g., drinking cold water/ice-slurry solution) cooling strategies mainly restrict the rise in body temperature and thereby increase the time to exhaustion [5,[8][9][10][11]. Wearing a cooling vest before exercise helps limit the core temperature increase [7,8,12,13] and improves the rating of perceived exertion (RPE) and thermal perceptions [13,14]-which, as behavioral controllers [15] can lead to a decrease in performance through an anticipatory and voluntary down-regulation of effort [16], thereby improving performance [6,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown the relevance of cooling strategies prior to exercise (pre-cooling) to limit the negative impact on aerobic performance [5][6][7][8]. Among these countermeasures, external (e.g., cooling vest, water immersion) and internal (e.g., drinking cold water/ice-slurry solution) cooling strategies mainly restrict the rise in body temperature and thereby increase the time to exhaustion [5,[8][9][10][11]. Wearing a cooling vest before exercise helps limit the core temperature increase [7,8,12,13] and improves the rating of perceived exertion (RPE) and thermal perceptions [13,14]-which, as behavioral controllers [15] can lead to a decrease in performance through an anticipatory and voluntary down-regulation of effort [16], thereby improving performance [6,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several cooling techniques have been attempted to achieve improved exercise performance, including immersion in cold water [7][8][9], and use of ice jackets and ice packs [8,10,11]. Recently, intake of ice slurry has drawn attention as an efficient method to obtain internal cooling without excessive reduction of the muscle temperature in hot environments [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Changing the physical state of water from the solid state to the liquid state requires a large transfer of heat energy. Accordingly, ice slurry provides a greater cooling effect than liquid water alone [15,16]. It has been reported that ingestion of 2 to 7.5 g/kg body mass of ice slurry attenuated the rise in the core body temperature during exercise [17][18][19].…”
Section: Introductionmentioning
confidence: 99%